2023
DOI: 10.1038/s41598-023-41922-8
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of category-specific word representations in a brain-constrained neurocomputational model of semantic dementia

Yury Shtyrov,
Aleksei Efremov,
Anastasia Kuptsova
et al.

Abstract: The neurobiological nature of semantic knowledge, i.e., the encoding and storage of conceptual information in the human brain, remains a poorly understood and hotly debated subject. Clinical data on semantic deficits and neuroimaging evidence from healthy individuals have suggested multiple cortical regions to be involved in the processing of meaning. These include semantic hubs (most notably, anterior temporal lobe, ATL) that take part in semantic processing in general as well as sensorimotor areas that proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…The image naming experiment conducted on 78 patients with semantic dementia (SD) in one study showed that the level of conceptual typicality was highly correlated with the completion of tasks by SD patients -the worse the typicality, the worse the results [6]. SD is an obstructive disease in understanding language meanings, believed to be associated with anterior temporal lobe (ATL) atrophy [7]. To verify this result, the researcher conducted the same experiment on 16 normal participants, and conducted transcranial magnetic stimulation interference on their 4 / 28 ATL area, obtaining similar results as the previous experiment.…”
Section: Concrete Conceptsmentioning
confidence: 99%
“…The image naming experiment conducted on 78 patients with semantic dementia (SD) in one study showed that the level of conceptual typicality was highly correlated with the completion of tasks by SD patients -the worse the typicality, the worse the results [6]. SD is an obstructive disease in understanding language meanings, believed to be associated with anterior temporal lobe (ATL) atrophy [7]. To verify this result, the researcher conducted the same experiment on 16 normal participants, and conducted transcranial magnetic stimulation interference on their 4 / 28 ATL area, obtaining similar results as the previous experiment.…”
Section: Concrete Conceptsmentioning
confidence: 99%
“…The image naming experiment conducted on 78 patients with semantic dementia (SD) in one study showed that the level of conceptual typicality was highly correlated with the completion of tasks by SD patients, the worse the typicality, the worse the results [6] . SD is an obstructive disease in understanding language meanings, believed to be associated with anterior temporal lobe (ATL) atrophy [7] . To verify this result, the researcher conducted the same experiment on 16 normal participants, and conducted transcranial magnetic stimulation interference on their ATL area, obtaining similar results as the previous experiment.…”
Section: Concrete Conceptsmentioning
confidence: 99%